The Mini Nutritional Assessment (R)-Its History, Today's Practice, and Future Perspectives - Bauer, Judith; Kaiser, Matthias J.; Anthony, Patricia; Guigoz, Yves; Sieber, Cornel (Nutrition in Clinical Practice, 2008)
In the early 1990s, the Mini Nutritional Assessment(R) (MNA; Nestle Nutrition, Vevey, Switzerland) was developed for nutrition screening in the elderly. Since then, it became the most established and widespread screening tool for older persons and has been translated into many different languages. The MNA shows prognostic relevance with regard to functionality, morbidity, and mortality of the elderly in different settings. This article recalls the development of the MNA with its short form (MNA-SF) and reviews the literature, focusing on the most recent publications. Specific features of the application of the MNA in different settings (community, nursing home, hospital) are considered. Minor shortcomings of the tool, such as the resources and the cooperation necessary for completion of the MNA, are discussed. Future options for the adaptation of this valuable tool are briefly characterized. (Nutr Clin Pract. 2008;23:388-396)
Keywords: nutrition assessment; nutrition status; aged; geriatrics; geriatric assessment; malnutrition; protein-energy malnutrition